Identifikasi Pengalaman Istri Mendapatkan Stigma Negatif dengan Kondisi Infertilitas - Suzanna Suzanna; Yudi Abdul Majid; Lita Gustina Tanda Bela (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to identify the wife's experience of getting negative stigma with infertility conditions in Palembang. This research method is a qualitative study with an empirical phenomenological approach and uses direct interviews. The number of participants in this study reached 12 people. The study's results show three themes that can describe the experience of a wife getting negative stigma with infertility conditions: the first theme is about deep feelings and loneliness with infertility conditions. This can be done by participants who feel lonely without a child's presence. The second theme concerns the negative stigma of a large family and society. The participants can say that they often get ridiculed by their neighbors and husband's family as barren wives. The third theme is about the wife's high hopes in marriage. This can be done by the participants who want offspring and to have a happy and peaceful life in their household. In conclusion, significant themes describe the wife's experience of getting negative stigma with infertility conditions, psychological problems arising from feelings of deep sadness and infertility, negative or lousy stigma given by society and family, and the wife's high hopes in marriage. Keywords: Infertility, Wife, Negative Stigma